The importance of elastography in hepatological diagnostics in children - Łężyk-Ciemniak, Eliza; Moppert, Justyna; Pawłowska, Małgorzata (Clinical and Experimental Hepatology, 2025)
About 30 years have passed since elastography was first used, with the greatest popularity in the last 10 years. The use of this diagnostic method is particularly important in patients with liver disease. FibroScan shows higher sensitivity in assessing the degree of organ steatosis and fibrosis compared to ultrasound. The noninvasive nature and ease of performance make it possible to perform the test in most pediatric patients. Owing to the correlation of the results with the histopathological evaluation, elastography replaces liver biopsy in many cases. Given the epidemic of childhood obesity observed in recent years, FibroScan testing appears to be increasingly necessary.